2002
DOI: 10.1002/cncr.10976
|View full text |Cite
|
Sign up to set email alerts
|

Decongestive lymphatic therapy for patients with breast carcinoma‐associated lymphedema

Abstract: BACKGROUNDDisruption of the lymphatic circulation through breast carcinoma‐associated axillary lymph node dissection, with or without radiation therapy, reportedly is the most common cause of lymphedema in developed countries. There is no cure for breast carcinoma‐associated lymphedema. Although intermittent pneumatic compression (IPC) has been acknowledged as a potential component of the multidisciplinary therapeutic strategy in the treatment of patients with breast carcinoma‐associated lymphedema, prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(68 citation statements)
references
References 28 publications
1
65
0
Order By: Relevance
“…PC has been used in lymphedema reduction treatment and it was concluded that no difference in reduction occurred in comparison with a control group (19) . Some studies associated components of CDT with pneumatic compression (20)(21) .…”
Section: Resultsmentioning
confidence: 99%
“…PC has been used in lymphedema reduction treatment and it was concluded that no difference in reduction occurred in comparison with a control group (19) . Some studies associated components of CDT with pneumatic compression (20)(21) .…”
Section: Resultsmentioning
confidence: 99%
“…In general, the treatment of lymphedema focuses on decreasing the swelling in the extremity, controlling symptoms, and reducing complications (17). Because lymphedema associated with PsA and rheumatoid arthritis can be related to the inflammation process, it is important to closely follow-up these patients and to take the disease under control in patients developing lymphedema (8).…”
Section: Discussionmentioning
confidence: 99%
“…(2) Intermittent pneumatic compression [17][18][19] In this procedure, a cuff is worn on the affected limb, and air is intermittently infused from the periphery of the affected limb toward the center for compression. Its therapeutic effects remain controversial.…”
Section: (1) Elevationmentioning
confidence: 99%